Synergistic impact of temperature and pore saturation on corrosion in carbonated reinforced concrete - Li Soon Wan; Mayuko Hirata; Toshinori Oyamoto; Tetsushi Kanda; Kang Hai Tan (Case Studies in Construction Materials)
Carbonation-induced corrosion in reinforced concrete (RC) structures significantly threatens their long-term durability, particularly in lower-strength concrete typical of 1960s-1970s buildings in high temperature regions like Singapore. Despite extensive research on individual factors affecting corrosion, the synergistic effects of temperature and pore saturation remain poorly understood in warmer climates. Current durability assessment tends to overestimate the service life of carbonated RC structures in tropical climates due to incomplete understanding of these combined effects. This study investigates the temperature-pore saturation relationship through systematic experimental variation (0–40 °C, 60–100 % pore saturation) using electrochemical and non-destructive measurements, aiming to develop accurate predictive tools for RC maintenance in tropical climates. Results revealed a critical phenomenon: minimum pore saturation threshold for severe corrosion decreases significantly with increasing temperature. For concrete with a water-to-cement ratio of 0.65, severe corrosion occurred at substantially lower pore saturation levels at higher temperatures, with even lower thresholds for more porous concrete. To translate these findings into practical tools, multiple linear regression analysis yielded predictive equations relating temperature and pore saturation effects to corrosion rates. Analysis also revealed that temperature-dependent corrosion kinetics, rather than concrete drying, predominantly drive the corrosion process at higher temperatures, explaining substantial corrosion activity even at lower pore saturation levels. These findings prompt a fundamental reassessment of models that rely on temperature-independent pore saturation thresholds, as they significantly underestimate corrosion risks in hot climates.